Clinical assessment of stereoscopic optic disc photographs for glaucoma: the european optic disc assessment trial - Reus, Nicolaas Johannes; Lemij, Hans G.; Garway-Heath, David F.; Airaksinen, P. Juhani; Anton, Alfonso; Bron, Alain M.; Faschinger, Christoph; Holló, Gábor; Iester, Michele; Jonas, Jost B.; Mistlberger, Andrea; Topouzis, Fotis; et al. (Ophthalmology, 2010)
Purpose - To determine the diagnostic accuracy of judging optic disc photographs for glaucoma by ophthalmologists. - Design - Evaluation of diagnostic test and technology. - Participants - A total of 243 of 875 invited ophthalmologists in 11 European countries. - Methods - We determined how well each participant classified 40 healthy eyes and 48 glaucomatous eyes with varying severity of the disease on stereoscopic slides. Duplicate slides were provided for determining intraobserver agreement. All eyes were also imaged with the GDx with variable corneal compensation (GDx-VCC) (Carl Zeiss Meditec AG, Jena, Germany) and the Heidelberg Retina Tomograph (HRT) I (Heidelberg Engineering GmbH, Heidelberg, Germany). Diagnostic accuracies of clinicians were compared with those of the best machine classifiers. - Main Outcome Measures - Accuracy of classification, expressed as sensitivity, specificity, and overall accuracy. Intraobserver agreement (κ). - Results - The overall diagnostic accuracy of ophthalmologists was 80.5% (standard deviation [SD], 6.8; range, 61.4%-94.3%). The machine classifiers outperformed most observers in diagnostic accuracy; the GDx-VCC nerve fiber indicator and the HRT's best classifier correctly classified 93.2% and 89.8% of eyes, respectively. The intraobserver agreement (κ) varied between −0.13 and 1.0 and was on average good (0.7). - Conclusions - In general, ophthalmologists classify optic disc photographs moderately well for detecting glaucoma. There is, however, large variability in diagnostic accuracy among and agreement within clinicians. Common imaging devices outperform most clinicians in classifying optic discs. - Financial Disclosure(s) - Proprietary or commercial disclosure may be found after the references.